Effect of Problem Based Learning Model on Mathematical Learning Outcomes of 6th Grade Students of Elementary School Accredited B in Kendari City - Andi Kaharuddin (SAINTIS Publishing, 2018)
The purpose of this study was to determine the effect of problem-based learning models towards the mathematics learning outcomes of 6th-grade students of an Elementary School accredited B in Kendari City. This study is quantitative experimental research. The population in this were all 6th-grade students of an Elementary School accredited B in Kendari City. The technique of determining the sample was done by cluster random sampling. Data analysis used is descriptive statistics and inferential statistics where the hypothesis test used is the t-test. The results showed the effect of problem-based learning models better than direct instruction and problem-based learning model positive effect on mathematics learning outcomes of 6th-grade students of an Elementary School Accredited B in Kendari City.